2008
DOI: 10.1007/s11605-007-0385-7
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes in Esophageal Cancer Patients with Tumor Recurrence After Curative Esophagectomy

Abstract: This study aimed to identify predictive factors and to evaluate appropriate treatments for recurrence of esophageal cancer after curative esophagectomy. About 166 consecutive patients, who underwent curative esophagectomy, were enrolled between April 1994 and March 2003. Recurrence was classified as loco-regional or distant. Logistic regression analysis was used to identify predictive factors for recurrence. Prognostic factors were evaluated by Log-rank test and Cox proportional hazard regression analysis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
69
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 25 publications
11
69
2
Order By: Relevance
“…Finally, the duration of follow-up was limited. Still, the majority of recurrences develop within 1 year, and more than 90% of them develop by the third year after surgery [22,23]. Thus, we believe that our follow-up period was long enough for comparing RFS among the groups.…”
Section: Discussionmentioning
confidence: 92%
“…Finally, the duration of follow-up was limited. Still, the majority of recurrences develop within 1 year, and more than 90% of them develop by the third year after surgery [22,23]. Thus, we believe that our follow-up period was long enough for comparing RFS among the groups.…”
Section: Discussionmentioning
confidence: 92%
“…As it has recently been shown that early treatment of recurrent disease might improve survival, it seems of utmost importance to detect recurrent lesions as early as possible [9]. The main argument for follow-up without imaging is that if a recurrent lesion is detected, few additional treatment options are available [13]. …”
Section: Introductionmentioning
confidence: 99%
“…However, patients with advanced disease still frequently develop recurrence, and the prognosis of these patients remains poor (21)(22)(23). To predict the treatment outcomes of patients with ESCC, it is important to understand the proliferative activity of ESCC tumor cells and its prognostic impact.…”
Section: Discussionmentioning
confidence: 99%